2008
DOI: 10.1177/0170840607088016
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Special Issue: Organization Studies as a Science for Design: Creating Collaborative Artifacts and Research

Abstract: He previously was on the staff of Maastricht University and Tilburg University. Georges Romme obtained a master's degree in economics from Tilburg University. In 1992 he received a doctoral degree in business administration from Maastricht University. His current research addresses design methodology, innovation, technology entrepreneurship and organizational learning. Georges has published several books and a large number of articles in Strategic Management Journal, Organization Science, Organization Studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 30 publications
0
73
0
8
Order By: Relevance
“…As the goal was to create knowledge and understanding to be used in solving managerial problems by building and applying a designed artefact (Jelinek, Romme, and Boland 2008), design science research methodology was seen especially applicable for this context. Although the DSR approach is quite new in management research (Jelinek, Romme, and Boland 2008;van Aken and Romme 2009;Sein et al 2011), it is widely used in IS research (Iivari 2007). The concept of a design artefact is broad, including models, methods, constructs, design theories, social innovations, and previously unknown properties of resources.…”
Section: Design Science Research and Doramentioning
confidence: 99%
“…As the goal was to create knowledge and understanding to be used in solving managerial problems by building and applying a designed artefact (Jelinek, Romme, and Boland 2008), design science research methodology was seen especially applicable for this context. Although the DSR approach is quite new in management research (Jelinek, Romme, and Boland 2008;van Aken and Romme 2009;Sein et al 2011), it is widely used in IS research (Iivari 2007). The concept of a design artefact is broad, including models, methods, constructs, design theories, social innovations, and previously unknown properties of resources.…”
Section: Design Science Research and Doramentioning
confidence: 99%
“…Romme and Endenburg (2006) previously proposed a five-step cyclical design process that makes explicit all of these themes and ideas, including the notion of design principles. Although the authors had originally focused on the specific problem of organization design (Dunar & Starbuck, 2006;Jelinek et al, 2008), other researchers have found the process to be both adaptable and extensible. For example, McPhee (2012a) introduced refinements for performance management and for linking design principles to specific actions, and proposed a results-based organization design process for technology entrepreneurs.…”
Section: A Design Science Perspectivementioning
confidence: 99%
“…Design science is increasingly applied in the domains of information systems (Hevner et al, 2004;Peffers et al, 2008;Pries-Hehi & Baskerville, 2008) and organization design (Dunbar & Starbuck, 2006;Jelinek et al, 2008;McPhee, 2012b), and a wide array of novel applications including policy design (Gilsing et al, 2010) and process design (Bryson et al, 2013). By developing and applying a design science perspective on secure critical infrastructures, we offer three contributions:…”
Section: Contributionmentioning
confidence: 99%
“…The topic has been discussed in several special issues of academic journals such as the Journal of Management Studies (Clark & Fin-cham, 2009) and Organization Studies (Jelinek, Romme & Boland, 2008). Traditionally, the problem has been framed either as a 'knowledge transfer problem' (lost in translation) or a 'knowledge production problem' (lost before translation) (Shapiro, Kirkman & Courtney, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%